O produtor familiar na pecuária leiteira : limites e potencialidades - Delfino, Alzemar José (2016)
The technological change is nowadays, comprehended as a playing field which involves cultural and economic processes of appreciation and depreciation of the social aspects of family unit. The exclusion of small producers from the activity is used as an argument to characterize that in the contemporary intercapitalist competition, the family ways of production take up restrict social positions of a technical progress and of a cultural and economic appreciation. The state, a coparcener of the modernization process, has its relevance as a financing agent, a technical capacitor, an infrastructure propitiator, that is, through macro and microeconomic policies which can create sustainable conditions to permit, mainly, not only the family producer to be inserted in the activity, but, above all, to remain in it. This way, this study aims to identify and analyze the family producer, through its limits and potentialities, with a thesis that this would be the main agent responsible for boosting the Brazilian milk production in quantity and quality. Therefore, results were compared obtained from a field survey with data collection via semi-structured open interviews in a sample of 108 producers effectively respondents, namely: 59 family farmers with active DAP (research focus) and 49 employers producers the municipality of Monte Alegre de Minas - MG. Technological indices were used to identify the developmental stage of the producers, thus allowing a comparative study between them. The field research covered all rural municipality of Monte Alegre de Minas – MG and, the result found that the majority of family farmers presented lower rates than technological employers producers. However, it allowed us to state also that the producer family and assisted by public policies, can be the agent of transformation of dairy farming.